Synthesis and Biological Evaluation of Some Novel Pyrimidine Derivatives - P, Muthumani (International Journal of Pharmaceutical & Biological Archive, 2010)
Synthesis of some novel pyrimidine derivatives has been done. The entire synthesized compounds were characterized by UV, IR and 1HNMR spectroscopy. The antimicrobial activity was evaluated. The present investigation deals with the synthesized compounds possessing good antimicrobial activity. Analgesic activity of the compounds by Eddy's hot plate method was evaluated against Diclofenac Sodium as the standard the tail flick response was considered as the end point to remove the animals from the source of the pain stimulus. The basal reaction time (latency between the application of the stimulus and the response) of the control animals ranged between (2.2 ± 0.33 - 3.3 ±0.33) after treatment of the animals the basal reaction time was prolonged (statistically significant increase) by the compounds (P1, P2, P6, P7 and P8) which reached maximum levels at the 2ndhr. However all the compounds showed analgesic activity less than the reference standard. The result of anti-inflammatory activity showed significant reaction in paw volume by the compounds P1 P2, P6, P7 and P8 when compared to control at (p < 0.01).